Pengaruh Pendekatan Matematika Realistik Berbasis Pemecahan Masalah Berbantuan Media Konkret Terhadap Hasil Belajar Matematika - Narayani, Ni Pt. Utami Dewi (Universitas Pendidikan Ganesha, 2019)
This study aimed at investigating the significant effect of realistic mathematic approach problem solving-based with concrete media towards mathematic achievement in fifth grade of elementary school in Gugus I Kecamatan Banjar Kabupaten Buleleng in academic year 2017/2018. This was a quasi-experimental research utilizing non-equivalent post-test only control group design. There were 134 students from fifth grade Gugus I Kecamatan Banjar Kabupaten Buleleng as the population of this study. The samples of this study were 60 students which consisted of 30 students from fifth grade of SDN 3 Kaliasem as experimental group and 30 students from fifth grade of SDN 3 Temukus as control group. The samples were chosen using random sampling technique. The data of mathematic achievement result collected by using method test with mathematic achievemen tresult test instrument, in from of multiple choice. The obtained data were analysed descriptively and inferentially t-test. The comparison of mean score from experimental and control group reveals that higher score than the control one (19,36>13,70). Hypothesis testing shows that tobserved is higher than t critical value (9,39>2,05) at the level of significance 5%, hence H0 is rejected and H1 is accepted. This indicates that investigating the significant effect of realistic mathematic approach problem solving-based with concrete media towards mathematic achievement in fifth grade of elementary school in Gugus I Kecamatan Banjar Kabupaten Buleleng in academic year 2017/2018.